A new species of Boesenbergia and rediscovery of B. rotunda (Zingiberaceae) from India - K., Aishwarya; Vinitha, M.r.; Thomas, George; Sabu, M. (Phytotaxa, 2015)
A new species of Boesenbergia from northeast India is described and illustrated. Besides, the rediscovery of B. rotunda from India after a century is reported. In addition to morphology, data from anatomy, molecular biology and pollen morphology are also used.